The passing of a champ: Newspaper coverage of Muhammad Ali's death - Satti, Mohamed (2018)
This study analyzed coverage of Muhammad Ali’s death in three newspapers: Khaleej Times, The Guardian and The New York Times. Guided by framing analysis, the one-week long coverage period between his death and his burial provided insight into how Ali was portrayed both inside and outside the ring. The study suggested four frames to this media coverage: Ali the celebrity, the entertainer, the humanitarian, and the man of the people. Results indicated that Ali was mostly portrayed as a celebrity and as a man of the people. Ali’s boxing prowess inside his ring and his outspoken nature outside of it ensured that he remained an instantly recognizable figure all over the world. Results also indicated that Ali was an inspiration to many since he stood up for his beliefs and against social injustices